2008
DOI: 10.1063/1.2918336
|View full text |Cite
|
Sign up to set email alerts
|

Structural properties of dusty plasma in direct current and radio frequency gas discharges

Abstract: This paper presents radial distribution functions of dust particles obtained experimentally in dc and rf discharges. Pressure and interaction energy of dusty particles were calculated on the basis of these functions. The Langevin dynamics computer simulation for each experiment was performed. The comparisons with computer simulations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 58 publications
(29 citation statements)
references
References 26 publications
(17 reference statements)
1
28
0
Order By: Relevance
“…1 [9]. The core part of the installation is represented by a vacuum-tight glass tube of 0,8 m in length and 0,06 m in diameter with discharge electrodes positioned at the top and bottom of it.…”
Section: Methodsmentioning
confidence: 99%
“…1 [9]. The core part of the installation is represented by a vacuum-tight glass tube of 0,8 m in length and 0,06 m in diameter with discharge electrodes positioned at the top and bottom of it.…”
Section: Methodsmentioning
confidence: 99%
“…1,2 By these reasons, the dusty plasma properties are actively investigated on the basis of the theoretical and experimental methods. [1][2][3][4][5] In the most cases, the dust particles have charge of the same sign. Hence, the forces affected between them are mostly repulsive.…”
Section: Introductionmentioning
confidence: 99%
“…Such wake effects that are due to a "focusing" of the light particles behind the heavy one are well known from classical dusty (complex) plasmas where ion focusing behind a highly charged heavy dust particle is well established experimentally, e.g. [12][13][14]. Recently, it has been shown that the presence of a strong ion drift leads to the excitation of ion instabilities and the destabilization of highly ordered dust grain ensembles such as dust crystals and to their melting [15], and also generalizations to magnetized plasmas have been performed [16].…”
Section: Introductionmentioning
confidence: 99%